The role of mobile money innovations in the effect of inequality on poverty and severity of poverty in Sub-Saharan Africa - Simplice Asongu; Sara Le Roux (African Governance and Development Institute (AGDI), 2023)
This study investigates the role of mobile money innovations in the incidence of income inequality on poverty and severity of poverty in 42 sub-Saharan African countries over the period 1980 to 2019. Mobile money innovations are understood as the mobile used to send money and the mobile used to pay bills online while income inequality is measured with the Gini index. Poverty is measured as the poverty headcount ratio while the severity of poverty is generated as the squared of the poverty gap index. The empirical evidence is based on interactive Quantile regressions. The following main findings are established. (i) Income inequality unconditionally reduces poverty and the severity of poverty though the significance is not throughout the conditional distributions of poverty and the severity of poverty. (ii) Mobile money innovations significantly moderate the positive incidence of income inequality on poverty and the severity of poverty in some quantiles. (iii) Positive net effects are apparent exclusively in the poverty regressions. (iv) Given the negative conditional effects, policy thresholds or minimum mobile money innovation levels needed to completely nullify the positive incidence of income inequality on poverty are provided: 27.666 (% age 15+) and 24.000 (% age 15+) of the mobile used to send money in the 50th and 75th quantiles, respectively and 16.272 (% age 15+) and 13.666 (% age 15+) of the mobile used to pay bills online in the 10th and 50th quantiles, respectively. Policy implications are discussed with respect of SDG1 on poverty reduction and SDG10 on inequality mitigation.
Keywords: G20; O40; I10; I20; I32; 330; Mobile phones; financial inclusion; poverty; inequality; Africa